Diagnostic and Therapeutic Approach in Intestinal Tuberculosis - Tri Hapsoro Guno; Barry A Putra; Telly Kamelia; Dadang Makmun (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2016)
Tuberculosis was still a global health problem. Beside lung, tuberculosis also manifest in other organs, one among them  is in abdominal organs. Abdominal tuberculosis was a complex disease with unspecific sign and symptoms so that its diagnostic procedure was not rarely inconclusive. We reported a 24 years old woman with chief complain of worsening abdominal pain in all region, accompanied by nausea, vomiting, bloating, and  absent bowel movement. She also had a fresh bloody stool. She had an active pulmonary tuberculosis on initiation phase treatment. Physical examination suggest a bowel obstruction sign with distended abdomen and increase bowel sound. Colonoscopy procedure findings was a mass that obstruct bowel lumen in ileocaecal region, suggest for malignancy similar to computerized tomography (CT) scan result, but pathlogic result showed an active colitis without any sign of malignancy. Because of its contradiction, the second colonoscopy was performed and concluded as intestinal tuberculosis, matched with second pathologic examination. Although polymerase chain reaction (PCR) tuberculosis (TB) showed a negative result, a further clinical judgement concluded this as an intestinal tuberculosis case. Patient was finally treated as intestinal tuberculosis with first-line antituberculosis drugs and planned to have colonoscopy evaluation. After general condition was good and obstructive ileus sign was relieved, patient planned for outpatient care.